The Mammalian Cervical Vertebrae Blueprint Depends on the T (brachyury) Gene. Issue 3 (22nd January 2015) - Kromik, Andreas; Ulrich, Reiner; Kusenda, Marian; Tipold, Andrea; Stein, Veronika M; Hellige, Maren; Dziallas, Peter; Hadlich, Frieder; Widmann, Philipp; Goldammer, Tom; Baumgärtner, Wolfgang; Rehage, Jürgen; et al.
Abstract: A key common feature of all but three known mammalian genera is the strict seven cervical vertebrae blueprint, suggesting the involvement of strong conserving selection forces during mammalian radiation. This is further supported by reports indicating that children with cervical ribs die before they reach reproductive age. Hypotheses were put up, associating cervical ribs (homeotic transformations) to embryonal cancer ( e.g., neuroblastoma) or ascribing the constraint in cervical vertebral count to the development of the mammalian diaphragm. Here, we describe a spontaneous mutation c.196A > G in the Bos taurus T gene (also known as brachyury ) associated with a cervical vertebral homeotic transformation that violates the fundamental mammalian cervical blueprint, but does not preclude reproduction of the affected individual. Genome-wide mapping, haplotype tracking within a large pedigree, resequencing of target genome regions, and bioinformatic analyses unambiguously confirmed the mutant c.196G allele as causal for this previously unknown defect termed vertebral and spinal dysplasia (VSD) by providing evidence for the mutation event. The nonsynonymous VSD mutation is located within the highly conserved T box of the T gene, which plays a fundamental role in eumetazoan body organization and vertebral development. To our knowledge, VSD is the first unequivocally approved spontaneous mutation decreasing cervical vertebrae number in a large mammal. The spontaneous VSD mutation in the bovine T gene is the first in vivo evidence for the hypothesis that the T protein is directly involved in the maintenance of the mammalian seven-cervical vertebra blueprint. It therefore furthers our knowledge of the T-protein function and early mammalian notochord development.